BAHAN AJAR KOMIK MATEMATIKA BERBASIS DIGITAL BAGI SISWA SEKOLAH DASAR - KUSUMADEWI, RIDA FIRONIKA; NEOLAKA, AMOS; Yasin, Mahmuddin (Phenomenon : Jurnal Pendidikan MIPA, 2020)
The purpose of this study was to determine the availability and use of teaching materials in schools, especially elementary schools. The teaching materials used are suitable for the students' needs. This study uses a Research and Development approach and method. The data collection technique here is to use interviews, teacher, and student response questionnaires to digital-based mathematics comic teaching materials. The field studies carried out include identifying the availability of teaching materials, analyzing the needs of teaching materials, analyzing learning, and identifying students' initial characteristic behaviors. The results of interviews based on field studies show that so far teachers have used conventional teaching materials, and only occasionally use digital-based teaching materials in the form of videos that are displayed on YouTube videos. Student response during learning so far is feeling less happy in participating in learning, especially learning mathematics, students' verbal ability in mathematics is still lacking. Based on these results, it is necessary to have teaching materials designed according to the needs and characteristics of students, namely by using digital-based comic teaching materials to improve the ability to understand mathematical concepts.Keywords: Teaching Materials, Mathematical Comic, Digital Abstract Tujuan dari penelitian ini adalah untuk mengetahui ketersediaan dan penggunaan bahan ajar disekolahan khususnya sekolah dasar. Bahan ajar yang digunakan apakah sesuai dengan kebutuhan siswa. Penelitian ini menggunakan pendekatan dan metode penelitian pengembangan (Research and Development). Teknik pengambilan data disini adalah menggunakan wawancara, angket respon guru dan siswa terhadap bahan ajar komik matematika berbasis digital. Studi lapangan yang dilakukan diantarannya adalah mengidentifikasi ketersediaan bahan ajar, melakukan analisis kebutuhan bahan ajar, melakukan analisis pembelajaran, dan mengidentifikasi perilaku karakteristik awal siswa. Hasil wawancara berdasarkan studi lapangan adalah, selama ini guru menggunakan bahan ajar konvensional, dan hanya sesekali menggunakan bahan ajar berbasis digital yang berbantu video yang ditampilkan melalui video youtube. Respon siswa selama pembelajaran selama ini adalah merasa kurang senang dalam mengikuti pembelajaran khususnya pembelajaran matematika, kemampuan siswa secara verbal pada pelajaran matematika juga masih sangat kurang. Berdasarkan hasil tersebut, maka sangat diperlukan adanya bahan ajar yang dirancang sesuai kebutuhan dan karakteristik siswa yaitu dengan menggunakan bahan ajar komik berbasis digital untuk meningkatkan kemampuan pemahaman konsep matematika.Kata kunci: Bahan Ajar, Komik Matematika, Digital